Duolingo Mobile Application as a Learning Tool in Improving the High School Students’ English Speaking Skill - Jaca, Cristie Ann; Justiniane, Milyn R.; Gabatilla, Grace P. (RIRAI Publisher, 2026)
This study investigated the use of the Duolingo Mobile Application in achieving English speaking proficiency among Grade 10 students in a public National High School in Cebu, Philippines. The researchers administered a pre-test and a post-test to compare the speaking proficiency of the two groups of students. A quasi-experimental design was applied in this study, which included two main variables: a dependent variable —Duolingo — and an independent variable —the students' speaking proficiency. This allowed for an investigation of the relationship, if any, between the use of Duolingo and the student's overall English communicative proficiency. Based on the findings of two independent tests, results reveal that students in the experimental group were able to reach a 53.9% improvement after the application of the proposed intervention, they were able to speak with complete confidence, and their speaking fluency exceeded that of the control group participants; they were able to reach only a 10.1% improvement. Overall, there was a significant difference in language proficiency between the two groups: participants in the experimental group improved many aspects of their oral skills, whereas those in the control group faced various challenges, including poorly formed sentences, a limited vocabulary, and a lack of confidence. The researchers concluded that the Duolingo Mobile Application aids in improving the students’ speaking skills. Moreover, this mobile application improves students' speaking abilities and can be recommended as a learning tool in English language instruction for high school students as it has proven its benefits in improving the student's speaking proficiency.